Aplikasi Cerdas Membantu Orang Tua Meningkatkan Kecerdasan Anak Dalam Pembelajaran Online Pandemi Covid -19 Dengan Algoritma C4.5. - Erika Fahmi Ginting; Khairi Ibnutama; Sri Kusnasari (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
During the current covid-19 pandemic, parents must play a direct role as teachers during online learning from school for their children at home. Knowing the potential intelligence of children is certainly important for parents. By analyzing the ability of the right and left brain, a child can be directed and developed according to their respective abilities. The ability of children's brains at the age of 6 to 12 years is very good to make parents and teachers more selective in determining suitable learning methods to apply them to children. The system that will be built in this research makes it possible to determine the potential of brain intelligence possessed by a child by classifying based on alternatives from the state of right brain or left brain intelligence provided in the database to determine the child's potential. The process of classifying the potential intelligence of children is carried out using the C4.5 Algorithm method pattern from the field of Data Mining. The results of this study are applications that can help parents understand the potential of a child. during the pandemic. The results of making the system that has been carried out have been tested using Rapid Miner and get accurasy results of 90% and classification error with a value of 10%.